Hyderabad Five-Year Plan Districtwise Distribution - Planning Commission (Planning Commission)
The problem that our Planners have set before themselves is first to formulate a Plan for the most effective and balanced utilisation of the country’s economic resources and then to determine priorities of works to be undertaken, define the stages in which the works should be carried out and propose the allocation of the available resources for the completion of each stage. Our Plan, as it stands, conveys the general nature of the task before us and is conceived in the interest of the community as a whole.
Hyderabad